ORGANIZATIONAL JUSTICE AMONG TEACHERS IN THE PRIVATE SCHOOLS IN TENKASI, TAMIL NADU (International Journal of Food and Nutritional Sciences, 2022)
Organizational justice refers to the idea that an action or decision is morally right, which may be defined according to ethics, religion, fairness, equity, or law, (Greenberg 1987). Descriptive research is particularly suited to explore questions, regarding the teachers. The respondents have considered 386sample teachers. It is found that the teachers are given more importance towards the express their views and feelings, applied consistently, free of bias, accurate information, procedures uphold ethical and moral standard.